Spiritual Education Practices in Islamic Religious Education Learning at SDN Krajan Sleman - Ogyaningrum; Hendro Widodo; Mahdee Maduerawae (Yayasan Azhar Amanaa Yogyakarta, 2023)
This study aims to explore and analyze the practice of spiritual education in PAI learning at SD Negeri Krajan Sleman. This research is a type of field research, using a qualitative descriptive approach. Data was collected through observation, interviews and documentation. The collected data was analyzed using a triangulation technique to identify the main issues related to spiritual education in PAI learning. The results of the study show that the practice of spiritual education in teaching PAI at SD Negeri Krajan Sleman has several aspects. First, PAI teachers use a holistic and integrative approach to integrate Islamic values into students' daily lives which emphasize understanding moral, ethical, and ethical values in each lesson. Second, PAI learning is designed to facilitate students' spiritual development by providing opportunities for students to reflect on themselves in praying collectively and individually. In addition, extracurricular activities such as religious studies, charity activities, and visits to places of worship are also carried out to strengthen students' spiritual education. Third, PAI teachers act as role models for students in practicing religious life while at school and provide assistance in implementing Islamic religious teachings by providing positive examples in everyday life.